(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The dried seeds flour of Diospyros mespiliformis was assessed for proximate, mineral and anti-nutritional composition using standard procedures. The results obtained from the proximate analysis were: moisture content (9.00 ± 0.00 g/100g), ash content (4.75 ± 1.06 g/100g), crude fat (2.22 ± 0.37 g/100g), crude fibre (2.67 ± 0.76 g/100g), crude protein (5.44 ± 0.88 g/100g), carbohydrate (76.35 ± 0.58 g/100g) and energy value (345.45 ± 0.58 kcal/100g). The mineral analysis showed that calcium is the most abundant element in the sample (180.26 ± 0.76 mg/100g), followed by magnesium (92.18 ± 1.24 mg/100g) and iron (90.48 ± 0.98 mg/100g) while zinc was the least (0.97 ± 0.73 mg/100g). The anti-nutritional factors analysed were oxalate (0.004 ± 0.00 mg/100g), phytate (0.880 ± 0.13 mg/100g), alkaloids (16.780 ± 4.29 mg/100g), flavonoid (29.300 ± 0.63 mg/100g), tannin (0.040 ± 0.98 mg/100g) and saponin (31.450 ± 2.12 mg/100g). The results from this study showed that the seeds of Diospyros mespiliformis has nutritional value comparable to conventional food crops, and can be used to replace calories and nutrients that could otherwise be derived from them during scarcity. However, further processing may be required when used as animal feed.